PENGARUH KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN, KEBIJAKAN DEVIDEN DAN PERTUMBUHAN EKONOMI TERHADAP NILAI PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN-PERUSAHAAN YANG TERDAFTAR DI INDEKS LQ45) - admin, MEILKY LIMANTO B11112036 (Jurnal Manajemen Update, 2016)
The firm’s value has become one of the firm’s objectives, as it becomes the firm’s framework in managing the company. The main purpose of the firm’s value in the long term is to increase the prosperity of the shareholders. This study aims to scrutinize the impact of investment decision, financial decision, dividend policies and the economic growth on the firm’s value in the firms listed in LQ45.   The method of this study uses the quantitative research, in which the research is based on the positivism philosophy used to examine the population and sample.  The type of data used in this study is the secondary data which has been collected by data gathering institutions and published to the data users in the society. The sample of this study is taken by using purposive sampling, in which the sample used must fulfill the following criterions: 1) The firms listed in LQ45 index during research period, 2) The complete data for financial reports is available during the research period, 3) The firms listed in LQ45 index gave dividend during the research period. The firms used as the sample are the firms listed in LQ45 index during the period of 2010 – 2014. The sample selection is based on the development of the Total Asset Growth, Debt to Equity Ratio, Gross Domestic Product, as well as Torbins Q. After the selection, the writer obtains the total sample of 17 firms which are able to fulfill the criterions as the sample. In this study, the writer used the panel regression estimation model by using the Generalized Least Square (GLS) approach. Whereas the hypothesis was tested by using the parametric statistic testing of Paired Sample T-Test. The results of the study shows that the investment decision negatively affects the firm value, the financing decision is found to have positive impact on the firm value, the dividend policies have a positive impact on firm value and the economic growth positively affects the firm value. Keyword : investment decision, financing decision, dividend policies and economic growth on the firm value